Mobile Foodscapes: a Case Study of Food Carts on Madison's Isthmus - Prendergast, Olivia; Grosenick, Sam; Quinn, Chloe (My University, 2012)
Our research investigates the food cart scene on Madison's Isthmus. City policies and regulations focus the density of food carts on Library Mall on the UW-Madison campus; however we emphasize in our narrative the social and spatial interactions that factor into the area's importance as a hub. Multiple interviews demonstrate that food cart location and design reflect the interactions of economics, policy, and producer-consumer dynamics as well as the constraints of physical geography. Ethnographic and landscape observations document the many social and spatial relationships tied to mobile food. These relationships include the close producer-consumer rapport encouraged by the carts, the social interaction fostered by the vibrant atmosphere, and the communal identities surrounding food, connected to the environment the carts create. The carts expand a culinary niche by bridging community and city involvement, and finally, encouraging food mobility, convenience, quality, and uniqueness.
Includes Photographs, Maps and Bibliography.
Keywords: Carts; Food; Madison, Wisconsin; Isthmus; Library Mall; University of Wisconsin Madison